2007
DOI: 10.1080/13813450701783513
|View full text |Cite
|
Sign up to set email alerts
|

The roles of hyperglycaemia and oxidative stress in the rise and collapse of the natural protective mechanism against vascular endothelial cell dysfunction in diabetes

Abstract: Vascular endothelial cell (VEC) dysfunction in diabetes has been associated with hyperglycaemia-induced intra- and extracellular glycation of proteins and to overproduction of glucose-derived free radicals. VEC protect their intracellular environment against an increased influx of glucose in face of hyperglycaemia by reducing the expression and plasma membrane abundance of their glucose transporter-1 (GLUT-1). We investigated the hypothesis that glucose-derived free radicals induce this down-regulatory mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 70 publications
2
43
0
1
Order By: Relevance
“…7). ROS and oxidative stress are known to regulate Glut-1 (17,18), and NO is known to have anti-oxidant properties (40). Thus, by decreasing ROS the observed increase in NO produced by heat shock would lead to the observed decrease Glut-1 and glucose uptake (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7). ROS and oxidative stress are known to regulate Glut-1 (17,18), and NO is known to have anti-oxidant properties (40). Thus, by decreasing ROS the observed increase in NO produced by heat shock would lead to the observed decrease Glut-1 and glucose uptake (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Next we determined whether there is was any difference in glucose transporters in these cells. It has been previously established that Glut-1 and Glut-2 are the major glucose transporters found in BAECs (14,17,18,23). The Western blots of Glut-1 and Glut-2 showed that the Glut-1 is very much reduced in heat-shocked cells, whereas there was no change in Glut-2 (Fig.…”
Section: Increased Hsp90⅐enos Interactions In Heat-shocked Cells and mentioning
confidence: 98%
See 2 more Smart Citations
“…Dois estudos adicionais avaliando desfecho em paciente com acidente vascular cerebral mostraram que hiperglicemia aguda e hiperglicemia de estresse prolongada estariam relacionadas a pior prognóstico e aumento da mortalidade, especialmente nos pacientes sem diagnóstico prévio de DM. 25,26 Umpierrez et al realizaram uma revisão com 2.030 pacientes e evidenciaram que a hiperglicemia hospitalar é um achado comum e representa um marcador de mau prognóstico e de mortalidade em pacientes com e sem história de DM. 17 Sechterberger et al realizaram um estudo com pacientes clínicos e cirúrgicos no qual constataram que glicemia média elevada e alta variabilidade dos níveis glicêmicos foram relacionadas à mortalidade na UTI em pacientes não diabéticos.…”
Section: Pacientes E Variáveisunclassified